Empedobacter brevis causing early onset sepsis and pneumonia in a neonate: case report and review of literature - Basani, Laxman; Aepala, Roja (International Journal of Contemporary Pediatrics, 2018)
Empedobacter brevis, a gram negative non-motile bacillus that belongs to the family Flavobacteriaceae rarely causes infection in adults and is exceptionally rare in neonates. E. brevis is ubiquitous in the environment, causing nosocomial infections especially in debilitated and immuno-compromised patients with only one case being reported in a neonate. We report a case of early onset sepsis and pneumonia in a term neonate caused by E. brevis that was successfully treated in our unit. Awareness regarding this uncommon pathogen and initiation of appropriate antibiotic therapy improves the outcome and prevents mortality. To the best of our knowledge, this is the second case of E. brevis sepsis reported in a neonate.